2017
DOI: 10.14198/elua2017.31.02
|View full text |Cite
|
Sign up to set email alerts
|

English-Russian cross-linguistic comparison of research article abstracts in geoscience

Abstract: Mastering the genre of the research article abstract is crucially important to meet the expectations of a discourse community in a particular scientific field. To date, research has shed light on how abstracts are written in various disciplines. However, few if any attempts have been made to analyse the abstract in geoscience. Furthermore, several studies have investigated the genre of abstract drawing on native/non-native, expert/apprentice dichotomies. Even so, there has not been sufficient investigation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Hedging in academic prose has been exhaustively investigated from conceptually different perspectives (Aull & Lancaster, 2014;Azar & Hashim, 2022;Belyakova, 2017;Gillaerts & van de Velde, 2010;Hu & Cao, 2011;Kozubíková Šandová, 2021;Lenardič & Fišer, 2021;Takimoto, 2015;Vassileva, 2001;Varttala, 2001). Previous studies have revealed that there are significant differences in the employment of hedging devices in RA abstracts across disciplines, cultures and time spans (Gillaerts & van de Velde, 2010;Hu & Cao, 2011;Khedri et al, 2015;Kozubíková Šandová, 2021).…”
Section: Hedging In Research Article Abstractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedging in academic prose has been exhaustively investigated from conceptually different perspectives (Aull & Lancaster, 2014;Azar & Hashim, 2022;Belyakova, 2017;Gillaerts & van de Velde, 2010;Hu & Cao, 2011;Kozubíková Šandová, 2021;Lenardič & Fišer, 2021;Takimoto, 2015;Vassileva, 2001;Varttala, 2001). Previous studies have revealed that there are significant differences in the employment of hedging devices in RA abstracts across disciplines, cultures and time spans (Gillaerts & van de Velde, 2010;Hu & Cao, 2011;Khedri et al, 2015;Kozubíková Šandová, 2021).…”
Section: Hedging In Research Article Abstractsmentioning
confidence: 99%
“…Hedging is an interesting element of academic writing pragmatically functioning as metadiscourse used to present claims with various degrees of tentativeness and to enter into a dialogue with readers. The employment of hedges in academic discourse has been examined in a large number of works, including those whose results have found applications in style manuals (Al-Khasawneh, 2017;Alonso Almeida, 2014;Alward et al, 2012;Aull & Lancaster, 2014;Belyakova, 2017;Gillaerts & van de Velde, 2010;Haufiku & Kangira, 2018;Hu & Cao, 2011;Hyland, 2005cHyland, , 2018Khedri et al, 2015;Kozubíková Šandová, 2021;Lenardič & Fišer, 2021;Lores Sanz, 2006;Lorés Sanz et al, 2010;Martín, 2003;Petchkij, 2019;Vassileva, 2001). However, as Crystal (1995, p. 117) put it, hedging is "a huge meadow of research", and knowledge of this metadiscourse resource can improve our understanding of how scholars work.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike these studies, which focused exclusively on the rhetorical organisation of RA abstracts of distinct disciplines, other studies examined other sources of variation, while focusing on specific disciplines. In particular, some studies have examined how abstracts of specific disciplines differ across languages (Belyakova, 2017;Marefat & Mohammadzadeh, 2013) Belyakova (2017) examined abstracts written by Russian novice researchers and English-speaking experts in Geoscience. Juan and Tao (2013) also compared medical abstracts across English and Chinese and found that Move 1 (research background) was nearly absent in the abstracts written by Chinese writers.…”
Section: Move Structure Of Ra Abstractsmentioning
confidence: 99%
“…Others have examined the linguistic features that characterise RA abstracts (Gillaerts, 2014;Kuhi & Mousavi, 2015). Essentially, previous research on RA abstracts has focused, among other things, on intra/cross-disciplinary, cross-linguistic, and cross-cultural variations (e.g., Al-Khasawneh, 2017; Belyakova, 2017;Dong & Xue, 2010;Ji, 2015;Marefat & Mohammadzadeh, 2013), using a corpus comprising abstracts from different journals. This has created a knowledge gap on the rhetorical organisation and linguistic features of abstracts of individual journals.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the existing variation reflects differences in the linguacultural and epistemological traditions of the Anglophone and Czech linguistics communities, which favor different rhetorical strategies when approaching writer-reader interaction. These studies conducted on English materials indicate the less intense use of hedges by non-native English writers (Belyakova 2017, Chen & Zhang 2017, Dontcheva-Navratilova 2016, Hu & Cao 2011, Ji 2015, Sládková 2017, Thuy 2018, Vassileva 2001, Yagiz & Demir 2014. At the same time, it has been found that different linguistic cultures use different functional categories to hedge in academic discourse: Vietnamese writers, for example, prefer modal verbs (Thuy 2018), while Iranian researchers often use adverbs, including approximators (Rezanejad 2015).…”
Section: Introductionmentioning
confidence: 99%